Carbon and Nitrogen Speciation in N-poor C-O-H-N Fluids at 6.3 GPa and 1100–1400 °C - Alexander G. Sokol (Nature Portfolio, 2017)
Abstract Deep carbon and nitrogen cycles played a critical role in the evolution of the Earth. Here we report on successful studying of speciation in C-O-H-N systems with low nitrogen contents at 6.3 GPa and 1100 to 1400 °C. At fO2 near Fe–FeO (IW) equilibrium, the synthesised fluids contain more than thirty species. Among them, CH4, C2H6, C3H8 and C4H10 are main carbon species. All carbon species, except for C1-C4 alkanes and alcohols, occur in negligible amounts in the fluids generated in systems with low H2O, but С15-С18 alkanes are slightly higher and oxygenated hydrocarbons are more diverse at higher temperatures and H2O concentrations. At a higher oxygen fugacity of +2.5 Δlog fO2 (IW), the fluids almost lack methane and contain about 1 rel.% C2-C4 alkanes, as well as fractions of percent of C15–18 alkanes and notable contents of alcohols and carboxylic acids. Methanimine (CH3N) is inferred to be the main nitrogen species in N-poor reduced fluids. Therefore, the behaviour of CH3N may control the nitrogen cycle in N-poor peridotitic mantle. Oxidation of fluids strongly reduces the concentration of CH4 and bulk carbon. However, higher alkanes, alcohols, and carboxylic acids can resist oxidation and should remain stable in mantle hydrous magmas.